Neuronal mitochondrial dysfunction and bioenergetic failure in inflammation-associated depression - Casaril, Angela Maria; Dantzer, Robert; Bas Orth, Carlos (Frontiers in neuroscience, 2021)
Depression is a leading cause of disability and affects more than 4% of the population worldwide. Even though its pathophysiology remains elusive, it is now well accepted that peripheral inflammation might increase the risk of depressive episodes in a subgroup of patients. However, there is still insufficient knowledge about the mechanisms by which inflammation induces alterations in brain function. In neurodegenerative and neuroinflammatory diseases, extensive studies have reported that inflammation negatively impacts mitochondrial health, contributing to excitotoxicity, oxidative stress, energy deficits, and eventually neuronal death. In addition, damaged mitochondria can release a wide range of damage-associated molecular patterns that are potent activators of the inflammatory response, creating a feed-forward cycle between oxidative stress, mitochondrial impairment, inflammation, and neuronal dysfunction. Surprisingly, the possible involvement of this vicious cycle in the pathophysiology of inflammation-associated depression remains understudied. In this mini-review we summarize the research supporting the association between neuroinflammation, mitochondrial dysfunction, and bioenergetic failure in inflammation-associated depression to highlight the relevance of further studies addressing this crosstalk.